(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This essay analyzes Il berretto a sonagli to discover its central topics, in connection with other Pirandello’s works. The focus is on the dialectic between the two concepts of “Subject” and “Truth”, to show in what way this relation affects the characters. Following the critical path suggested by the author, the result leads to verify the existence of a social “machine”, in which Ciampa plays its role.